34 USE OF PROPHYLACTIC ANTICOAGULATION AND THE RISK OF HEPATIC VENO-OCCLUSIVE DISEASE IN PATIENTS UNDERGOING HEMATOPOIETIC STEM CELL TRANSPLANTATION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (1st March 2006) - Imran, H.; Tleyjeh, I. M.; Zirakzadeh, A.; Rodriguez, V.; Khan, S. P.
Abstract : Context: Hepatic veno-occlusive disease is one of the most serious regimen-related toxicities in patients undergoing hematopoietic stem cell transplantation. The prophylactic use of anticoagulation remains controversial. Objective: To perform a systematic review and meta-analysis of the literature on the effect of anticoagulation in preventing veno-occlusive disease. Data Sources: MEDLINE, EMBASE, and several other databases were searched. Study Selection: We identified randomized controlled trials and cohort studies that compared the use of unfractionated heparin or low-molecular-weight heparin for prevention of veno-occlusive disease with a nontherapeutic control in children and adults undergoing hematopoietic stem cell transplantation. Data Extraction: Two investigators independently identified eligible studies and assessed their quality. Data Synthesis: Twelve studies were eligible, with a total of 2, 782 patients. Anticoagulation prophylaxis was associated with a statistically nonsignificant decrease in the risk of veno-occlusive disease (pooled relative risk 0.90; 95% CI 0.62-1.29). Relative risk estimates differed according to the type of transplant recipient, study design, intervention, and outcome definition. However, all the cohort studies had methodologic limitations, including biases in selection and comparability. The results of 1 of 3 randomized controlled trials may have been affected by delayed introduction of anticoagulation. A second trial enrolled patients who received conventional chemoradiotherapy and were in an early stage of their disease. The relative risk was 0.18 (95% CI 0.04-0.78), but the trial had limited generalizability. The third trial was a pilot study with a small sample size (relative risk 0.74; 95% CI 0.53-1.04). Conclusions: Significant heterogeneity and methodologic weaknesses preclude drawing a meaningful conclusion from the pooled analysis, but the results of 2 randomized control trials suggest that prophylactic anticoagulation may help prevent veno-occlusive disease. However, a large randomized controlled trial is needed for confirmation.